2020
DOI: 10.2298/vsp171213055m
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acutely and subchronically applied DL-methionine on plasma oxidative stress markers and activity of acetylcholinesterase in rat cardiac tissue

Abstract: Background/Aim. Chronically induced hypermethioninemia leads to hyperhomocysteinemia which causes oxidative stress, atherogenesis, neurodegeneration and cancer. However, little is known about the acute and subchronic effects of DL-methionine (Met). The aim of study was to assess the effects of acutely and subchronically applied Met on oxidative stress parameters in rat plasma [enzymes: catalase (CAT), glutathione peroxidise (GPx), superoxide dismutase (SOD) and index of lipid peroxidation, malondialdehyde (MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…stress plays an important role in the pathophysiology of HHcy and its complications [5,6]. A number of studies have shown that elevated plasma total-Hcy level is associated with Alzheimer's disease, atherogenesis, neurodegeneration and cancer [7]. Therefore, the plasma total-Hcy level has been used as a metabolic disorder parameter in clinic [8,9,10].…”
mentioning
confidence: 99%
“…stress plays an important role in the pathophysiology of HHcy and its complications [5,6]. A number of studies have shown that elevated plasma total-Hcy level is associated with Alzheimer's disease, atherogenesis, neurodegeneration and cancer [7]. Therefore, the plasma total-Hcy level has been used as a metabolic disorder parameter in clinic [8,9,10].…”
mentioning
confidence: 99%